2020
DOI: 10.1002/jor.24812
|View full text |Cite
|
Sign up to set email alerts
|

Effects of in vivo cyclic compressive loading on the distribution of local Col2 and superficial lubricin in rat knee cartilage

Abstract: This study aimed to examine the effects of an episode of in vivo cyclic loading on rat knee articular cartilage (AC) under medium‐term observation, while also investigating relevant factors associated with the progression of post‐traumatic osteoarthritis (PTOA). Twelve‐week‐old Wistar rats underwent one episode comprising 60 cycles of 20 N or 50 N dynamic compression on the right knee joint. Spatiotemporal changes in the AC after loading were evaluated using histology and immunohistochemistry at 3 days and 1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…This study has several limitations. First, the cyclic loading model used in this study in rat is not able to produce PTOA-like changes in the whole joint 33 . Although the current animal model was adequate to achieve the purpose of this study to examine protective effect of KUS121 on the suppression of acute chondrocyte death, one of the crucial early events in OA, other OA models would be needed to evaluate the effect of KUS121 on whole joint OA changes.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…This study has several limitations. First, the cyclic loading model used in this study in rat is not able to produce PTOA-like changes in the whole joint 33 . Although the current animal model was adequate to achieve the purpose of this study to examine protective effect of KUS121 on the suppression of acute chondrocyte death, one of the crucial early events in OA, other OA models would be needed to evaluate the effect of KUS121 on whole joint OA changes.…”
Section: Discussionmentioning
confidence: 92%
“…Rats were intraperitoneally administered a combination anaesthetic containing 0.375 mg/kg medetomidine, 2 mg/kg midazolam, and 2.5 mg/kg butorphanol, and were randomly assigned into vehicle-or KUS121-treated groups (6 rats per group). The cartilage injury was exposed by cyclic compression as previously reported 33 . Briefly, each right knee was placed in a prone position on a custom-made table with the knee at approximately 140° flexion and subjected to cyclic compressive loading including a pre-load of 5 N, peak load of 20 N with an approaching speed of 1 mm/s, and a 10 s rest interval.…”
Section: Rat Model Of Post Traumatic Osteoarthritis Induced By Cyclicmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the cartilage explants displayed an increased coefficient of friction demonstrating that injurious load significantly compromises tissue function [168]. Application of 60 cycles of injurious compressive load (20 and 50 N) on rat knees in vivo resulted in a transient reduction in lubricin within the lesions that formed on the lateral femoral condyles [169]. The detrimental effects of high-magnitude, high-strain-rate injurious loading regimens are thought to result as a consequence of cellular damage, such as chondrocyte apoptosis and necrosis [170].…”
Section: Injurious Loadsmentioning
confidence: 99%
“…One session of cyclic compression, with a peak load of 20 ​N and 60 cycles, was applied to the rat's knee [ 9 ]. We demonstrated that this one-session cyclic compression could lead to regional cytopenia and loss of glycosaminoglycan (GAG), which is an important functional component of the extracellular matrix (ECM) [ 15 ], and simultaneously, to no immediate structural damage. However, we did not observe further OA pathological progression of OA 8 weeks after compression.…”
Section: Introductionmentioning
confidence: 99%